On multi-group neutron transport in planar one dimensional geometry: A solution for a localized pulsed source. (March 2017) - Fernandes, J.C.L.; Bodmann, B.E.J.; Vilhena, M.T.
Highlights: The present work presents a solution to the multi-group neutron transport equation. The novelty consists in an analytical representation of the solution. A stability analysis for the round solution is presented. Abstract: In this work we present a solution for the multi-group neutron transport equation in planar one dimensional geometry. As an application we consider a scenario with a localized pulsed source. The basic idea of this work consists in constructing a recursive system of equations leading to an analytical representation for the multi-energy group solution. The error control is obtained by properly choosing the recursion depth of the equation system. The authors also present an analysis of stability for the results of the recursive system. Numerical simulations are reported for a problem with pulsed neutron source.